Does Covid scare wine travelers? Evidence from France and Italy - Giulia Gastaldello; Florine Livat; Luca Rossetto (Wine Economics and Policy, 2022)
Tourism is sensitive to shocks, and the Covid pandemic has profoundly changed sector dynamics. Although wine tourism is primarily a form of proximity tourism, the pandemic may have affected wine travellers behaviour and intention to go on a wine holiday. This exploratory study proposes a comprehensive analysis of the impact of Covid-related fear and anxiety on wine tourism intentions after the first lockdown while jointly considering the effects of solidarity, situational and personal involvement with wine. An online survey was delivered to a sample of 553 wine tourists from Italy and France, two major wine tourism destinations. Results highlight changes in wine travel patterns after the pandemic, which boosted post-lockdown wine tourism intentions. Indeed, the latter are poorly impacted by fear of contagion while it is enhanced by dedicating time to wine in lockdown (i.e., situational involvement) and by willingness to support local wine producers. Implications for sectors stakeholders are suggested.
Keywords: 330; Covid phobia; Covid-19; involvement with wine; solidarity; structural equation modelling; travel intentions; Wine tourism